PICES Press, Vol. 24, No. 1, Winter 2016 - North Pacific Marine Science Organization (PICES) (North Pacific Marine Science Organization (PICES), 2016)
PICES science in 2015: A note from the Science Board Chairman (pp. 1-7); 2015 PICES awards (pp. 8-10); Face to face with oceanographers: PICES outreach (pp. 11-13); An update on the FUTURE science program (pp. 14-15); International Scientific Symposium on “Harmful algal blooms and climate change” (pp. 16-17); International Scientific Conference on “Our common future under climate change” (pp. 18-19); PICES/ICES Workshop on “Modelling effects of climate change on fish and fisheries” (pp. 20-23); The mussel Mytilus galloprovincialis on Japanese tsunami marine debris (pp. 24-28); Moving towards more sustainable shrimp and tilapia aquaculture in Karawang, Indonesia (pp. 29-30); New leadership in PICES (pp. 31-21); Alexander S. Bychkov – Connecting regional organizations on a global scale (pp. 33-33); Japanese translation of “Guide to Best Practices for Ocean CO2 Measurements” (pp. 34-34); Global ocean carbon dioxide (CO2) uptake: Distribution and temporal variation (pp. 35-35); For the e-bookshelf: “Impacts of the Fukushima Nuclear Accident on Fish and Fishing Grounds” (pp. 36-37); PICES interns (pp. 38-38); PICES calendar of events (pp. 39-39); The state of the western North Pacific during the 2015 warm season (pp. 40-41); The Bering Sea: Current status and recent trends (pp. 42-45); The Blob (Part Three): Going, going, gone? (pp. 46-48)